Respuesta :
Simplify:
A(n) = -6 + (n - 1)(6) = -6 + (n)(6) + (-1)(6) = -6 + 6n - 6 = 6n - 12
Put n = 1, n = 4 and n = 10 to the expression:
A(1) = 6(1) - 12 = 6 - 12 = -6
A(4) = 6(4) - 12 = 24 - 12 = 12
A(10) = 6(10) - 12 = 60 - 12 = 48
Answer:
first term = -6, fourth term = 12 and tenth term = 48.
-6, 12, 48
Answer:
-6,12 and 48.
Step-by-step explanation:
A(n) = –6 + (n–1)(6)
This is the the nth term.
The first term is obtained when we use n = 1:-
First term A(1) = -6 + (1 -1)(6) = -6 + 0
= -6.
To find the fourth term we replace n by 4 :
A(4) = -6 + (4 - 1)(6)
= -6 + 18
= 12.
In a similar way the 10th term
= -6 + (10-1)(6)
= -6 + 54
= 48 .